2006
DOI: 10.1177/153944920602600203
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Validity of the Canadian Occupational Performance Measure in a Posttraumatic Stress Program

Abstract: The Canadian Occupational Performance Measure (COPM) was adapted to a group format and used to investigate self-perceived change over time with respect to treatment goals in a sample of adults with histories of child abuse who participated in a 6-week inpatient trauma program. Using the COPM, 177 adults developed individualized goals and rated their performance and satisfaction with performance of these goals at admission, discharge, and 3, 6, and 12 months post-discharge. Goals were classified into six catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The remaining four papers reported use of the COPM as an evidencedbased outcome measure and all supported the use of the COPM to measure client report of change. Chesworth et al (2002) and Harper et al (2006) documented client report of effectiveness in self-identifi ed areas of occupational performance over time. However, Stevens et al (2003) measured change in only one participant, and Brown et al (2001) measured change in only eight participants.…”
Section: Client-centred Interventionmentioning
confidence: 99%
“…The remaining four papers reported use of the COPM as an evidencedbased outcome measure and all supported the use of the COPM to measure client report of change. Chesworth et al (2002) and Harper et al (2006) documented client report of effectiveness in self-identifi ed areas of occupational performance over time. However, Stevens et al (2003) measured change in only one participant, and Brown et al (2001) measured change in only eight participants.…”
Section: Client-centred Interventionmentioning
confidence: 99%
“…Moreover, the COPM has been shown to be an adaptable tool for highlighting problem areas in mental health [54] and has been found to have satisfactory validity [20][21][22][24][25][26]55] and reliability [19,20], thus enhancing the probability of satisfactory credibility in the present study.…”
Section: Methodological Considerationsmentioning
confidence: 62%
“…The COPM has shown satisfactory internal consistency, and moderate [19] to good [20] test-retest reliability for performance and satisfaction scores. The discriminant validity has been confirmed [20,21], and the COPM has been shown to have satisfactory content validity [22,23], criterion validity [24], construct validity [22,24], concurrent validity [25,26], convergent validity [21], and responsiveness to change [27]. The Swedish version of the COPM [28], used in this study, has shown high responsiveness to change [29] and satisfactory clinical utility [30,31].…”
Section: Instrumentmentioning
confidence: 75%
“…Total performance and satisfaction scores were calculated by dividing the sum scores on each subscale by the number of assessed problems (18). The COPM has shown construct validity, reliability and responsiveness to change in several studies (19)(20)(21), adequate concurrent validity among patients with psychological distress (22) and validity and sensitivity to change among patients with low back pain and general persistent or chronic pain (4,23). The COPM aids in formulating individual patient goals within a multidisciplinary pain programme (4) and facilitates client-centred treatment (19).…”
Section: Data Collectionmentioning
confidence: 99%
“…The postal 1-year follow-up COPM form contained the same occupational problems. A postal follow-up procedure has been described as reliable (22,24). To further strengthen this procedure, a pilot study was made to ensure that a postal questionnaire was reliable in the present rehabilitation context.…”
Section: Data Collectionmentioning
confidence: 99%